Sensitivity Analysis of C. auris, S. cerevisiae, and C. cladosporioides by Irradiation with Far-UVC, UVC, and UVB - Anna-Maria Gierke; Martin Hessling (Case Western Reserve University, 2024)
Background: The World Health Organization has published a list of pathogenic fungi with prioritizing groups and calls for research and development of antifungal measures, with Candida auris belonging to the group with high priority. Methods: The photosensitivity towards short wavelength ultraviolet irradiation (Far-UVC, UVC, and UVB) was investigated and compared to other yeasts (Saccharomyces cerevisiae) and a mold (Cladosporium cladosporioides). The observed 1-log reduction doses were compared to literature values of other representatives of the genus Candida, but also with S. cerevisiae, Aspergillus niger, and A. fumigatus. Results: For the determined 1-log reduction doses, an increase with higher wavelengths was observed. A 1-log reduction dose of 4.3 mJ/cm2 was determined for C. auris when irradiated at 222 nm, a dose of 6.1 mJ/cm2 at 254 nm and a 1-log reduction dose of 51.3 mJ/cm2 was required when irradiated with UVB. Conclusions: It was observed that S. cerevisiae is a possible surrogate for C. auris for irradiation with Far-UVC and UVB due to close 1-log reduction doses. No surrogate suitability was verified for C. cladosporioides in relation to A. niger and A. fumigatus for irradiation with a wavelength of 254 nm and for A. niger at 222 nm.